THE CRUCIAL ROLE OF MUSIC IN PRESCHOOL EDUCATION - Dawletiyarova Venera Madyarovna (Journals Park Publishing, 2023)
Preschool education lays the foundation for a child's academic, social, and emotional development. In recent years, educators and researchers have increasingly recognized the profound impact that music can have on preschoolers. Music, with its captivating melodies and rhythmic patterns, plays a pivotal role in enhancing various aspects of early childhood education.
Keywords: preschool education, music, cognitive development, language development, social skills, emotional regulation, motor skills, cultural expression, listening skills, parental involvement, confidence, adaptability, resilience, interdisciplinary learning.